Increase Public Trust With Interaction Quality and Outcome Quality Through Satisfaction and Social Media - Risma RAUETA; Agus David RAMDANSYAH (PT Keberlanjutan Strategis Indonesia, 2026)
This research aimed to develop a basic theoretical model and a new empirical one to resolve the gap in previous research results regarding the role of Interaction Quality and Outcome Quality on Public Trust through Public Satisfaction and social media. This research uses descriptive and explanatory quantitative methods. The population in this study are people in Serang City with social media accounts aged 15 - 64 years who have experienced or received public services from BNN Banten Province. The sampling technique in this study used a non-probability sampling technique, namely the purposive sampling method. The data analysis technique uses Partial Least Square (PLS) with SmartPLS software. The results of the study are known: Interaction quality has a positive and significant effect on public trust; Interaction quality has a positive and significant effect on public satisfaction; Outcome quality has a positive and significant effect on public trust; Outcome quality has a positive and significant effect on public satisfaction; Public satisfaction has a positive and significant effect on public trust; Social media has a positive and significant effect on public trust; Social media moderates the effect of interaction quality on public trust.